Alleviating Effect of Calcium on Nickel Toxicity in Rice. Issue 6 (4th February 2015) - Aziz, Humera; Sabir, Muhammad; Ahmad, Hamaad Raza; Aziz, Tariq; Zia‐ur‐Rehman, Muhammad; Hakeem, Khalid Rehman; Ozturk, Munir
<x xml:space="preserve">Abstract</x> Urbanization and industrialization have resulted in contamination of soils with heavy metals and other pollutants. Nickel (Ni) is one of the toxic metals, which adversely affect plant growth by altering different physiological and metabolic processes. Mineral nutrients can reduce toxic effects of Ni on physiological and metabolic functions of plants, thus improving plant growth. The role of calcium (Ca) to alleviate Ni toxicity in rice was investigated. Rice plants were grown with Ni (20 and 40 mg kg−1) and Ca (80 and 160 mg kg−1) in different combinations and without Ni and Ca as a control. Nickel (40 mg kg−1) significantly decreased shoot (54%) and root dry weights (54%), chlorophyll content (57%), the photosynthetic rate (two‐fold), transpiration rate (34%) and stomatal conductance (39%) compared to control. Application of Ni (40 mg kg−1) increased the Ni concentration in shoots 22‐fold and in roots 11‐fold compared to control. Application of Ca (160 mg kg−1) reduced the adverse effects of Ni and the studied parameters improved to the maximum values compared to control. Calcium decreased the translocation of Ni towards the shoots that was evident from a lower translocation factor (42%) for the plants supplied with Ca compared to those grown without Ca (62%). The phytotoxicity induced by Ni on different growth and physiological parameters was alleviated by Ca as indicated by the minimum values of the phytotoxicity index for Ca fed plants (0) compared to those without Ca (2.6).